(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2008)
The ammonoid fauna of the Prati di Stuores/Stuores Wiesen section (Dolomites, north-eastern Italy) was studied in detail. This section was proposed as stratotype for the Carnian GSSP, with the first appearance of Daxatina cf. canadensis as primary marker, based on preliminary data. The validity of this proposal is confirmed by the present study, which integrates collections from the Prati di Stuores/Stuores Wiesen section and from others, particularly Bec de Roces (Passo Campolongo) and Antersass (Badia Valley). Ammonoids collected in these localities belong to three biostratigraphic units: regoledanus, canadensis and aon subzones. These subzones constitute, in the Southern Alps, the Ladinian/Carnian boundary interval. Regoledanus Subzone: the north American species Zestoceras enode is most probably documented in this biostratigraphic interval. Canadensis Subzone: the base is marked by the first appearance of Daxatina canadensis, and at least, another north American species, Daxatina laubei, seems to be present. Two species of Zestoceras were found: Z. barwicki e Z. lorigae sp.n. Two species of Trachyceras, distinct from T. aon, are represented in the canadensis Subzone: T. muensteri and T. bipunctatum. These species predate the first appearance of Trachyceras, justifying the canadensis Subzone to be included in the Carnian also on the basis of nomenclatural stability. Other significant taxa of this subzone are Rossiceras? armatum and Sirenotrachyceras thusneldae. Aon Subzone: the ammonoid fauna of this subzone is extensively treated in existing literature and thus not further discussed. Taxonomical notes and stratigraphic consequences: the new subfamily Anolcitinae (family Trachyceratidae) is erected. At present, Frankites regoledanus, F. apertus and F. sp. A have been recognized in the Southern Alps. The lectotype of Ammonites (Trachyceras ?) Regoledanus was defined. The latter species is exclusive of the regoledanus Subzone, whereas the distribution of the two other species encompasses the defined GSSP. The shell morphology of F. apertus and the north American species F. sutherlandi is identical. The suture line is also comparable, hence the two species are considered synonyms. This synonymy is relevant for long-distance correlations. The lectotypes of Trachyceras ruturanum and T. laricum were also defined.